Agricultural Innovation Dissemination Strategy in Rice Commodities Welcoming the Digitalization Era as an Effort to Support Sustainable Agricultural Development - Irmayani, Irmayani; Azis, Dina Aprianty; Abdullah, Abdullah; Ikbal PB, Muh. (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
This study aims to disseminate the technology package that has been used by farmers, namely the use of Rice Transplanter. Rice transplanter technology can foster changes in farming activities which include changes in the knowledge, skills, attitudes and actions of their family farmers through increasing knowledge, skills and attitudes. By changing the behavior of farmers and their families, it is hoped that they can manage their farming business productively, effectively and efficiently. The long-term goal is to improve the standard of living and welfare of farmers, which is directed at the realization of technical improvements (better farming), improved farming (better business), and better living for farmers and their communities. The method of determining the population and sample in this study uses the Proportional Random Sampling technique because the population used consists of several farmer groups in several villages and sub-districts in Sidenreng Rappang Regency, which has a food crop commodity sector, especially rice plants. The stages start from the input collection (the input stage), the scouting stage (the matching stage) and the strategy determination stage (the decision stage). The results showed that the role of innovation and farmer response in supporting agricultural development in Sidenreng Rappang Regency in the use of Rice Transplanter was good and the use of rice transplanter was considered as a technology that was able to help farmers effectively and efficiently.